THE EFFECT OF ACTIVE LEARNING STRATEGY USING THE THREE STAGE OF FISHBOWL DECISION TYPES ON THE RESULT OF HISTORY LEARNING - Basri, Wahidul (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
The ability of students of SMAN 1 Bukittinggi in studying history, especially in interpreting the facts are still low. To overcome these problems the writer try to applied active learning strategies Three Stage of Fishbowl Decision types (TSFD). The purpose of this study is to determine the effect of the use of active learning strategies on learning outcomes of TSFD type in the result of studying history, especially in the interpretation of historical facts. This research is experimental with Pretest-Posttest Control Group Design research. The results showed that active learning strategies of the type of TSFD were good for interpreting historical fact. However, after further analysis based on the pattern of growth or movement changes, in the process of active learning strategies of TSFD type was suitable to be applied. Furthermore, for the facts are based on royal topics of TSFD strategy that has turned out as good for the material that is repetition. Based on the analysis conducted it is believed that active learning strategies of TSFD type is better used on materials that complete require repetition.